2017
DOI: 10.1002/mbo3.482
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of the complex microbial consortium associated with cultures of the oil‐rich alga Botryococcus braunii

Abstract: Microalgae are widely viewed as a promising and sustainable source of renewable chemicals and biofuels. Botryococcus braunii synthesizes and secretes significant amounts of long‐chain (C30‐C40) hydrocarbons that can be subsequently converted into gasoline, diesel, and aviation fuel. B. braunii cultures are not axenic and the effects of co‐cultured microorganisms on B. braunii growth and hydrocarbon yield are important, but sometimes contradictory. To understand the composition of the B. braunii microbial conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Metagenomic analysis has also been performed on these microorganisms. For instance, Sambles et al [35] used high-throughput Illumina sequencing and 16S rDNA analysis to study the microbial composition of Botryococcus braunii at diverse treatments. The microbial analysis is also crucial in understanding other important components during the bioprocessing of microalgae, such as biofouling of photo-bioreactors [36].…”
Section: Biofuelmentioning
confidence: 99%
“…Metagenomic analysis has also been performed on these microorganisms. For instance, Sambles et al [35] used high-throughput Illumina sequencing and 16S rDNA analysis to study the microbial composition of Botryococcus braunii at diverse treatments. The microbial analysis is also crucial in understanding other important components during the bioprocessing of microalgae, such as biofouling of photo-bioreactors [36].…”
Section: Biofuelmentioning
confidence: 99%
“…For that reason, wastewater treatment with algaebacteria consortia is treated separately in Section 6. The molecular survey of bacterial diversity in three cultures (Nannochloropsis salina from a raceway pond and a closed photobioreactor, respectively, and Botryococcus braunii from laboratory flasks) (Carney et al, 2016;Sambles et al, 2017;Fulbright et al, 2018) and one biofilm sample from an outdoor photobioreactor (mixture of Chlorella vulgaris and Scenedesmus obliquus) (Krohn- Molt et al, 2013) revealed that Deltaproteobacteria and Gammaproteobacteria in raceway pond and Alphaproteobacteria and Bacteroidetes in closed bioreactor were dominant in N. salina, whereas Gammaproteobacteria, Betaproteobacteria and Firmicutes were the most prominent phyla in B. braunii. Alphaproteobacteria, Bacteroidetes, Betaproteobacteria and Gammaproteobacteria made up nearly three-quarters of the biofilm bacterial community.…”
Section: Alga-associated Bacteria In Algae Production Systemsmentioning
confidence: 99%
“…Visible light can act to regulate a sensory module in Caulobacter crescentus in order to increase the biochemical activity and cellular signaling for cell-surface and cell-cell attachment (Purcell et al, 2007). Asticcacaulis was detected in the microbial consortium of the oil-rich green alga Botryococcus braunii (Sambles et al, 2017). In the constant light treatment, continuous uptake of nutrients by the autotrophs, which included those in medium and the Chlorella symbionts inside the P. bursaria, probably lead to nutrient limitation to heterotrophic bacteria in the medium.…”
Section: Warming Selected Specific Bacterial Species In Association Wmentioning
confidence: 99%